The proposal of the design object of mapuche culture entrepreneurs: Araucanía, Chile - Álvarez Saavedra, Eugenia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The following article presents the incorporation of recycled materials in the manufacture of design articles, referring to cases of Mapuche women entrepreneurs in Chile. Although the design is elaborated through methodologies for innovation, the search and investigation og women entrepreneurs, it grants and adds value in the production chain and aesthetics. The proposal in the selection of materials such a plastic, will be a determining factor when designing and making design objects for a local market.